Exposure of healthy volunteers to swine house dust increases formation of leukotrienes, prostaglandin D2, and bronchial responsiveness to methacholine. Issue 12 (1st December 1998) - O'Sullivan, Siobhan; Dahlen, Sven-Erik; Larsson, Kjell; Larsson, Britt-Marie; Malmberg, Per; Kumlin, Maria; Palmberg, Lena
Abstract : BACKGROUND: Acute exposure of healthy subjects to swine house dust causes increased bronchial responsiveness to methacholine but no acute bronchoconstriction. The role of cysteinyl leukotrienes and mast cells in increased bronchial responsiveness is unclear. METHODS: Ten non-asthmatic subjects were exposed to swine dust for three hours while weighing pigs in a piggery. Urine was collected prior to and for up to 12 hours after entering the piggery and at the same times five days before and the day after exposure. As indices of whole body leukotriene production and mast cell activation, urinary levels of leukotriene E4 (LTE4 ) and 9α, 11β-PGF2, the earliest appearing urinary metabolite of prostaglandin D2 (PGD2 ), were measured. Bronchial responsiveness to methacholine was determined five days before and the day after the exposure. RESULTS: Methacholine PD20 FEV1 decreased from 1.32 mg (95% CI 0.22 to 10.25) before exposure to 0.38 mg (95% CI 0.11 to 1.3) after exposure (p<0.01). Associated with the increase in bronchial responsiveness there was a significant mean difference between post- and pre-challenge levels of LTE4 (difference 38.5 ng/mmol creatinine (95% CI 17.2 to 59.8); p<0.01) and 9α, 11β-PGF2 (difference 69 ng/mmol creatinine (95% CI 3.7 to 134.3); p<0.05) on the day of exposure to swine dust. Swine dust exposure induced a 24-fold increase in the total cell number and a 12-fold increase in IL-8 levels in the nasal lavage fluid. The levels of LTB4 and LTE4 in nasal lavage fluid following exposure also increased 5.5-fold and 2-fold, respectively. CONCLUSIONS: The findings of this study indicate that cysteinyl leukotrienes and other mast cell mediators contribute to the development of increased bronchial responsiveness following inhalation of organic swine dust.